Comparison of Single Versus Multiple Doses of Fluoroquinolone (Levofloxacin) for Prophylaxis in Prostate Biopsy - Iqbal Nasim, Faraz Khalid, Faraz Basharat Khan, Aatif Hassan Shaikh, Rajab Ali, Hira Anis Bumbia (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the efficacy of Levofloxacin 500 mg orally for prophylaxis in transrectal prostate biopsy guided by ultrasonography compared to three dosages. Study design: A comparative study Place and Duration: this study was done in Murshid Hospital and Health Care Centre Karachi from September 2021 to September 2022 Methodology: A total of 615 patients having the typical indications for prostate biopsy performed under transrectal ultrasonography guidance (increased PSA, abnormal digital rectal examination) were included in this study. Overall 425 patients were considered qualified for participation; using Graph Pad Prism 6.0, patients were assigned to one of two groups using random assignment, 205 individuals in Group A were given one oral dosage of 500 mg of levofloxacin 60 to 120 minutes before the procedure, Likewise, 220 patients in Group B received Levofloxacin (500 mg) once per 24 hours for two days before to the procedure as well as the day of it. Results: Patients in Group A were given orally a single dose of levofloxacin 500 mg there were 205 patients in this group. These individuals were diagnosed with diabetes mellitus (DM) at a rate of 43.9%, febrile urinary tract infections at a rate of 4.3%, and sepsis at a rate of 0.97%.In this group, 65.80cc,was the average prostate volume, and 90.17% were overweight.A total of 220 patients in groupB who received orally three doses of levofloxacin 500 mg, with an average age of 67.45 years and a PSA mean of 21.26 ng/mL; 31.8% of patients had diabetes mellitus, & 4.45% had a febrile urinary tract infection (FUTI). In this group, no patients had sepsis, 75.61 cc was the mean prostate volume, and 72.74% of the patients were overweight, as in Group A. Conclusion: Because of how effective it is, a single dose of levofloxacin containing 500 milligrams is an excellent option for prophylaxis in patients who are going to have a transrectal prostate biopsy. Keywords: transrectal biopsy, flroquinolone, prophylaxis